Recrudescence of a high parasitaemia, severe Plasmodium falciparum malaria episode, treated by artesunate monotherapy - Sophie Landre; Anne-Lise Bienvenu; Patrick Miailhes; Paul Abraham; Marie Simon; Agathe Becker; Anne Conrad; Guillaume Bonnot; Yobouet Ines Kouakou; Christian Chidiac; Gilles Leboucher; Thomas Rimmelé; et al. (International Journal of Infectious Diseases, 2021)
A patient presenting with severe malaria, with hyperparasitaemia, received 7-day artesunate monotherapy. A severe recrudescence was detected and attributed to hyperparasitaemia, monotherapy and a polyclonal infection without Kelch 13 gene mutation. A second treatment with artesunate, then quinine, followed by artemether-lumefantrine, was successful.